Molecular dynamics simulations of classical sound absorption in a monatomic gas. (12th May 2018) - Ayub, M.; Zander, A.C.; Huang, D.M.; Cazzolato, B.S.; Howard, C.Q.
Abstract: Sound wave propagation in argon gas is simulated using molecular dynamics (MD) in order to determine the attenuation of acoustic energy due to classical (viscous and thermal) losses at high frequencies. In addition, a method is described to estimate attenuation of acoustic energy using the thermodynamic concept of exergy. The results are compared against standing wave theory and the predictions of the theory of continuum mechanics. Acoustic energy losses are studied by evaluating various attenuation parameters and by comparing the changes in behavior at three different frequencies. This study demonstrates acoustic absorption effects in a gas simulated in a thermostatted molecular simulation and quantifies the classical losses in terms of the sound attenuation constant. The approach can be extended to further understanding of acoustic loss mechanisms in the presence of nanoscale porous materials in the simulation domain. Highlights: Study on classical acoustic losses in a gas using Molecular Dynamics (MD) simulations. Describes a method to estimate acoustic losses using thermodynamic concept of exergy. A simulation framework for MD has been developed to study sound absorption. Demonstrates the utility of MD method to study acoustic absorption at the nanoscale. Presents acoustic flow behavior in transition regime.